A comparative study on microstructure, nanomechanical and corrosion behaviors of AlCoCuFeNi high entropy alloys fabricated by selective laser melting and laser metal deposition. (20th December 2022) - Ren, Yaojia; Wu, Hong; Liu, Bin; Liu, Yong; Guo, Sheng; Jiao, Z.B.; Baker, Ian
Highlights: Hierarchically heterogeneous microstructures exist in both SLM- and LMD-processed specimens. Core-shell FCC precipitates in LMD bear 110 texture at high surface energy and high strain energy. Hot cracks occurred in both types of specimens due to the incompletely suppressed cu segregation. A correlation mechanism between microstructure, nano-mechanics, and corrosion behavior was obtained. Abstract: The present study investigated the microstructure, nanomechanics, and corrosion behavior of AlCoCuFeNi high entropy alloys fabricated by selective laser melting (SLM) and laser metal deposition (LMD). The microstructure of SLM-processed specimens was mainly composed of columnar-grained BCC matrix (∼90 µm in width) and Cu-rich twinned FCC phase. The columnar grains grew epitaxially along the building direction and exhibited a strong 001 texture. In comparison, a coarse columnar-grained BCC matrix (∼150 µm in width) with a stronger 〈001〉 texture, rod-like B2 precipitates, and large core-shell structured FCC phases were formed in the LMD-processed specimens due to the higher heat accumulation effect. Consequently, the LMD-processed specimens showed a lower hardness, wear resistance, and corrosion resistance, but higher creep resistance and reduced Young's modulus than the SLM-processed specimens. Hot cracks occurred in both types of specimens, which could not be completely suppressed due to Cu segregation.